Cardiovascular Status in the Hypoglycemic Type II Diabetic Subjects - Dr. Ajay Meshram, Dr. Sarmistha Sarkar, (International Journal of Innovative Research in Medical Science, 2017)
Introduction: Diabetes mellitus (DM) is a group of metabolic diseases which if not controlled can cause life threatening complications. Aim: To evaluate Cardiovascular Status in the Hypoglycemic Type II Diabetic Subjects. Methodology: Fasting blood glucose (FBG), glycated hemoglobin (HbA1c), total cholesterol (TC), high density lipoprotein (HDL), low density lipoprotein (LDL), very low density lipoprotein (VLDL), triglyceride (TG) and Microalbumin levels were evaluated. Total sample size was 60, which was divided into 30 study group with type II DM having hypoglycemia (blood glucose level <70 mg/dl) who attended the Medicine OPD of AVBRH Hospital and 30 age, sex matched healthy controls included in the study. Results: Results of serum lipid profile showed that the mean values for TC, TG, HDL, LDL and VLDL in study group were 228.50 ± 30.75, 152.10 ± 40.98, 40.73 ± 6.58, 153.13 ± 27.74 and 33.33 ± 9.93 mg/dL, respectively. TC, TG and LDL level were significantly higher in the cases as compared to controls (p<0.0001). Mean value for HbA1c in the study group was 6.94± 0.47, which was significantly higher in the cases as compared to the controls (p<0.0001) and the mean value for FBS in the study group was 61.43 ± 2.84, which was significantly lower in the cases as compared to the controls (p<0.0001). Mean value for Microalbumin levels in the study group were 70.71 ± 5.57 respectively, which were significantly higher in the cases as compared to the controls (p<0.0001). HbA1c has significant negative correlation with HDL (p<0.01). Conclusion: Early detection of lipid profile abnormalities along with microalbuminuria can minimize the risk for development of cardiovascular complications in the hypoglycemic type II diabetic patients.